Handling Sickle Cell Disease - LaPierre, Yvette, 1963-; Pradhan-Sundd, Tirthadipa (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2022)
Learn about sickle cell disease, which is the name under which multiple types of blood disorders are grouped, including the most common and severe type known as sickle cell anemia
Includes index.
Bibliography: pages 106-109.
Keywords: Anemia, Sickle Cell; Genetic disorders